2020
DOI: 10.1101/2020.04.19.043117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A calcium-based plasticity model predicts long-term potentiation and depression in the neocortex

Abstract: Long-term potentiation (LTP) and long-term depression (LTD) of pyramidal cell connections are among the key mechanisms underlying learning and memory in the brain. Despite their important role, only a few of these connections have been characterized in terms of LTP/LTD dynamics, such as the one between layer 5 thick-tufted pyramidal cells (L5-TTPCs).Comparing the available evidence on different pyramidal connection types reveals a large variability of experimental outcomes, possibly indicating the presence of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…For synapses, we used the Blue Brain Project’s synapse model with NMDA receptors, VGCCs, and calcium-based long-term plasticity model (Chindemi, Abdellah, Amsalem, Benavides-Piccione, Delattre, Doron, Ecker, King, Kumbhar, Monney, Perin, Rössert, van Geit, et al, 2020); details of the synaptic and calcium dynamics can be found there. The calcium-based plasticity model itself is based on (Graupner & Brunel, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For synapses, we used the Blue Brain Project’s synapse model with NMDA receptors, VGCCs, and calcium-based long-term plasticity model (Chindemi, Abdellah, Amsalem, Benavides-Piccione, Delattre, Doron, Ecker, King, Kumbhar, Monney, Perin, Rössert, van Geit, et al, 2020); details of the synaptic and calcium dynamics can be found there. The calcium-based plasticity model itself is based on (Graupner & Brunel, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a model synapse was developed as part of the Blue Brain Project (Chindemi, Abdellah, Amsalem, Benavides-Piccione, Delattre, Doron, Ecker, King, Kumbhar, Monney, Perin, Rössert, Geit, et al, 2020) which incorporates NMDA receptors, VGCCs, and calcium-dependent long-term plasticity dynamics. This synapse model (with some modifications described below in Methods ) enables us to explore Lisman’s hypothesis about the calcium basis of heterosynaptic plasticity in a dendritic cable model, which provides insight into the spatial properties of heterosynaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the dendrite is a single compartment, the precise spine location is undefined. For more detailed morphological simulations to predict plasticity see Ebner et al (2019), Chindemi et al (2020) and Jędrzejewska-Szmek et al (2017) . The distance from the soma to the spine functionally mimics the BaP attenuation as shown in Golding et al (2001) , and it is set to 200 μm for all simulations, except in Figure 3-Figure Supplement 6c and Figure 3-Figure Supplement 5e .…”
Section: Methodsmentioning
confidence: 99%
“…An alternative approach taken by several groups ( Bhalla and Iyengar, 1999; Jędrzejewska-Szmek et al, 2017; Blackwell et al, 2019; Chindemi et al, 2020; Zhang et al, 2021 ) was to model the complex molecular cascade leading to synaptic weight changes. The main benefit of this approach is the direct correspondence between the model’s components and biological elements, but this comes at the price of a large number of poorly constrained parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have tried to establish if calcium alone can account for synaptic plasticity (Shouval et al, 2002 ; Rackham et al, 2010 ; Chindemi et al, 2020 ), but given the involvement of multiple mechanisms based on dendrite biophysics (Froemke et al, 2010 ), presynaptic NMDA receptors (Wong et al, 2021 ) or NMDA receptors that signal unconventionally (Dore et al, 2017 ), metabotropic glutamate receptors (Nevian and Sakmann, 2006 ), and learning mechanisms residing in a third cell such as astrocytes (Min and Nevian, 2012 ; Adamsky et al, 2018 ), can we really hope to find one calcium model that fits all synapse types? If the calcium hypothesis in synaptic plasticity is not valid for all synapse types, then can we at least establish a phenomenological model that captures plasticity at all synapses?…”
Section: Is There a Grand Unifying Theory Of Synaptic Learning Rules?mentioning
confidence: 99%